1981
DOI: 10.1007/bf00388254
|View full text |Cite
|
Sign up to set email alerts
|

The compartmentation of carboxylating and decarboxylating enzymes in guard cell protoplasts

Abstract: Guard cell and mesophyll cell protoplasts of Vicia faba L. were purified and separated into cytoplasmic and plastid fractions by a selective silicone-oil filtration. Before fractionation, the protoplasts were ruptured by a low speed centrifugation through a narrow-aperture nylon net placed in a plastic vial. This protoplast homogenation and subsequently the silicone-oil fractionation offer the possibility of investigating the comparatmentation of the enzymatic carboxylating (ribulose bisphosphate carboxylase E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 25 publications
0
48
1
1
Order By: Relevance
“…These observations indicate that CO2 uptake and proton pumping in guard cells are regulated by light quality and imply that, in dark-adapted guard cells irradiated with white light, bluelight dependent proton pumping appears to be the predominant response. This interpretation might partially explain the discrepancy between the present results obtained under red light irradiation and previously reported experiments with white light, which have led to the conclusion that guard cells are devoid of PCRP activity (14,15,19) (see Outlaw [12] for review).…”
Section: C02 Fixation In Guard Cell Protoplastscontrasting
confidence: 90%
“…These observations indicate that CO2 uptake and proton pumping in guard cells are regulated by light quality and imply that, in dark-adapted guard cells irradiated with white light, bluelight dependent proton pumping appears to be the predominant response. This interpretation might partially explain the discrepancy between the present results obtained under red light irradiation and previously reported experiments with white light, which have led to the conclusion that guard cells are devoid of PCRP activity (14,15,19) (see Outlaw [12] for review).…”
Section: C02 Fixation In Guard Cell Protoplastscontrasting
confidence: 90%
“…This Supported by grants from the Deutsche Forschungsgemeinschaft to K. R. (Ra 122/11) and R. S. (Sche 217/3). conclusion was confirmed by metabolite determinations in mechanically isolated pairs of guard cells (13) as well as in suspensions of guard-cell protoplasts (21).…”
mentioning
confidence: 60%
“…PPDK is found also in seeds (1,12) and leaves (1) of wheat and in some other C3 plant tissues (for references, see 2). The role of PPDK in C3 leaf tissues is not clearly known, although it has been suggested that it might be involved in the control of stomatal opening (16). The occurrence of PPDK in developing wheat seeds does not correlate quantitatively with photosynthetic enzymes (2), and it was suggested that one role of the enzyme might be in the conversion of C3 amino acids, especially alanine, to C4 and C5 amino acids.…”
mentioning
confidence: 99%